Hydroxypropyl-Inulin as a Novel Encapsulating Agent of Fish Oil by Conventional and Water-Free Spray Drying - Gimenez-Castillo, B (Elsevier B.V., 2021)
Hydroxypropyl-inulin (HPI) was synthetized from inulin by etherification. The hydroxypropylation of inulin (degree of substitution 0.7) was confirmed by 1H NMR. The replacement of hydroxyl groups in inulin by an ether linkage increased its hydrophobicity, making HPI suitable as a novel encapsulating agent of fish oil (FO) by both conventional and water-free spray drying. FO microparticles were designed according to a composite central plus star statistical design. A FO-in-water emulsion was prepared as infeed for encapsulation by conventional spray drying (FO-csd), whereas FO was dispersed in methanol for encapsulation by water-free spray drying (FO-wfsd). The encapsulation efficiency of FO was similar in both FO-csd and FO-wfsd microparticles (80.5% and 82.6%, respectively), despite the different encapsulation mechanism. FO-wfsd microparticles showed lower glass transition temperature (Tg), hygroscopicity, moisture and water activity (aw) than FO-csd microparticles. Only the superficial FO was released from FO-wfsd microparticles (at pH 4.6 and 6.5) and FO-csd (at pH 6.5), which is desirable in the design of healthy food liquid matrices. Furthermore, FO-csd microparticles showed lower oxidative stability than FO-wfsd microparticles evaluated by the formation and distribution of polar compounds, suggesting that water had a higher plasticizing effect than methanol and provided FO microparticles with poor film-forming properties. The type of solvent determined the FO encapsulation mechanism but slightly affected the physico-chemical properties of the microparticles, the oxidative stability and the FO released pattern. © 2020